The Effect of Price Strategy and Product Quality on Customer Loyalty Mediated by Customer Satisfaction Variables in Tiara Convection Tulungagung - Arwina, Reonada; Nur Singgih, Moh.; Earlike A. S, Fitria (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the effect of price strategy and product quality on customer loyalty, both directly and indirectly through customer satisfaction as a mediating variable. The research was conducted on active customers of Tiara Konveksi Tulungagung, a small and medium-sized enterprise (SME) in the garment industry serving orders for school, organizational, and institutional uniforms in East Java. A quantitative approach with a survey method was used. Data were collected through questionnaires distributed to 350 respondents and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS 3 software. The results show that price strategy and product quality have a positive and significant effect on customer loyalty, both directly and indirectly through customer satisfaction. Price strategy significantly enhances customer satisfaction and loyalty, while product quality also contributes positively to satisfaction and long-term customer retention. Customer satisfaction plays a mediating role in strengthening the relationship between price strategy and loyalty, as well as between product quality and loyalty. This research emphasizes that in the garment industry, customer loyalty is not built solely on price or product quality, but on the overall customer experience, including value perception, service, and satisfaction. Therefore, businesses such as Tiara Konveksi are encouraged to apply competitive pricing strategies, maintain consistent product quality, and enhance customer satisfaction to foster sustainable loyalty.